Canopy Performance and Root System Structure of New Genotypes of Zoysia spp. During Establishment Under Mediterranean Climate - Diego Gómez de Barreda; Antonio Lidón; Óscar Alcantara; Cristina Pornaro; Stefano Macolino (Agronomy, 2025)
In a hypothetical climate change scenario, zoysiagrass species could be a good choice for turfgrass areas due to their adaptation to heat conditions and the great variability in species and cultivars. Knowledge of the root system’s characteristics is paramount for predicting cultivar adaptation to different heat–drought scenarios and therefore for designing proper turfgrass management programs, especially irrigation. A field experiment was conducted in the Mediterranean environment of Valencia (Spain) to study the root weight density (RWD), root length density (RLD), and average root diameter (RDI) at three different soil depths (0–5, 5–15, and 15–30 cm) of five new zoysiagrass genotypes (Zoysia matrella (L.) Merr., Zoysia japonica Steud., and their hybrid), relating these parameters to the performance of these experimental lines during their establishment. All the tested experimental lines had a higher RWD and RLD in the upper soil layer (0–5 cm), while the RDI was higher in the lowest layer of the sampled soil profile (0.269 mm compared with 0.249 mm and 0.241 mm in the upper layers). All the tested genotypes showed the same RWD and RLD, while the Zoysia matrella experimental line A showed a higher RDI value (0.2683 mm) than those for the Z. japonica (0.2369 mm) and the hybrid (0.2394 mm) genotypes. This last finding could have influenced its more rapid establishment, although it was not linked to its NDVI values during autumn. In conclusion, different morphological root characteristics were detected among new zoysiagrass genotypes and soil depths, which could have affected their canopy performance, and they are expected to affect irrigation management in a possible future drought scenario.